2024
DOI: 10.3310/grnm5147
|View full text |Cite
|
Sign up to set email alerts
|

The effects of computerised decision support systems on nursing and allied health professional performance and patient outcomes: a systematic review and user contextualisation

Abstract: Background Computerised decision support systems (CDSS) are widely used by nurses and allied health professionals but their effect on clinical performance and patient outcomes is uncertain. Objectives Evaluate the effects of clinical decision support systems use on nurses’, midwives’ and allied health professionals’ performance and patient outcomes and sense-check the results with developers and users. Eligibility criteria Comparative studies (randomised controlled trials (RCTs), non-randomised trials, contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 86 publications
0
2
0
Order By: Relevance
“…Accordingly, another study [48] investigating patient safety has observed that most of the dimensions considered were performing at international benchmarks, with a few performing better than the benchmarks. To improve the performance on several composites of patient safety, CDSSs could be an effective interventional approach, supporting the front-end staff such as nurses in ensuring a positive patient safety culture by empowering them in enhanced decision-making, improved efficiency, and time savings, providing consistent care, enhanced collaboration with other teams, reduced documentation, and support in complex cases [23][24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, another study [48] investigating patient safety has observed that most of the dimensions considered were performing at international benchmarks, with a few performing better than the benchmarks. To improve the performance on several composites of patient safety, CDSSs could be an effective interventional approach, supporting the front-end staff such as nurses in ensuring a positive patient safety culture by empowering them in enhanced decision-making, improved efficiency, and time savings, providing consistent care, enhanced collaboration with other teams, reduced documentation, and support in complex cases [23][24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…Studies [23][24][25][26][27] have identified that a CDSS can provide significant benefits to nurses by enhancing their ability to deliver safe, efficient, and effective patient care. Major benefits include: (a): enhanced decision-making: they provide nurses with evidence-based recommendations and guidelines, assisting them in making informed decisions about patient care.…”
Section: Introductionmentioning
confidence: 99%